2007
DOI: 10.1111/j.1471-0528.2007.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of anal sphincter rupture during vaginal delivery: faecal incontinence and sexual complaints

Abstract: Objective To determine the long-term effects of obstetric anal sphincter rupture on the frequency of faecal incontinence and sexual complaints.Design Retrospective case-control study.Setting Department of Gynaecology and Obstetrics, Ikazia Hospital, The Netherlands.Population All 171 women operated for anal sphincter rupture between 1971 and 1990 and 171 controls matched for parity and date of delivery.Methods Postal questionnaires regarding faecal incontinence were sent in 1996 and 2005 to all cases and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
5
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 23 publications
7
65
5
7
Order By: Relevance
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…The results of this study suggested that women with anal sphincter disruption had a slightly increased risk of fecal incontinence with no impact on urinary or sexual symptoms and mental or physical health [11]. In contrast, other authors reported a higher incidence of urinary symptoms [12,13] and sexual dysfunction [5,7,14,15] after anal sphincter tear.…”
Section: Introductionmentioning
confidence: 54%
“…To estimate a sample size, we used five studies that evaluated fecal incontinence after an anal sphincter tear [5,6,9,13,14]. Based on these studies, the overall fecal incontinence rate was 40% (21-57%) and 20% (7-32%) for women with and without an anal sphincter tear, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anxiety about resumption of an active sex life after OASR and its deleterious effect on sexual function have been described in earlier studies. [23][24][25][26] Participants told of shame and guilt due to the reduction in sex life and its effects on their partner. Bearing in mind the anxiety and iso-lation which the women felt, it seems highly likely that partners also feel similar emotions, and therefore have the same needs for discussion, support, and information.…”
Section: Inability To Function Sexuallymentioning
confidence: 99%